Gesture politics or real commitment?: Gender inequality and the allocation of aid - Dreher, Axel; Gehring, Kai; Klasen, Stephan (World development, 2015)
We investigate whether donors give more aid to countries with larger gender gaps in education, health, or women’s rights, and whether they reward improvements in those indicators. We find some evidence that high gender gaps in education and health are associated with higher allocation of aid in those sectors and aid overall. Greater female political representation also appears to come along with higher aid flows. While we find no systematic evidence that donors allocate funds with regard to merit, our results show that donors are more responsive to inequalities in countries that provide good legal rights for women.